Topical lidocaine helps reduce pain of digital ulcers in systemic sclerosis (scleroderma) - Ozgocmen, S; Kaya, A; Coskun, BK (Springer, 2006)
Sir, Digital ulcerations are prominent features of systemic sclerosis ( SSc; scleroderma) and can occur for various reasons. Ulcerations can be very painful, thereby limiting functions, and healing with scarring and/ or digital resorption and when infected can lead to serious soft tissue infections and osteomyelitis. Ulcerations reportedly occur in approximately one third of patients with SSc per year, and the etiology appears to be multifactorial. Ischemia, vasculitis, and traumas are the most commonly encountered causes for digital ulcers [ 1, 2]. Herein, we report a single case of a scleroderma patient whose pain of digital ulcers could be successfully managed by an application of topical lidocaine. A 47- year- old woman with a 10- year history of SSc ( limited SSc) presented with very painful digital ulcers on her hands and feet. She complained of Raynaud's phenomenon on her upper limps. The initiation of these ulcers was simultaneous with minor traumas while doing housework. She complained of sharp pain on her fingers and of knife- wound sensation over the lesions on the dorsum of the hand and foot fingers, soles, and heels. She had a history of depression, hypertension, and osteoporosis.